(3JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFYs - (3Ydj Hf eMeO Hf ehSi Hf eeSYhO GdNRGYjs ((3CMeO Hf eMeO GdeQRcGhi GdJWGhfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb ef ZjQ EaJbGQ Edjge hHSW GdQRb LhOkG efg Ydjge hHYO aEfi deG QCjJ cKjQkG eef de JQSN ai GdeYGQa bOeg hdjS dOjg ef COhGJ GdWdH EdG eOGOg hbdeg hSejJg JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf ai YgO QShd Gddg Udi Gddg Ydjg hSs
(3BNQgG (B:s
(3hcJGH GdcaGjI hGdZfG ai CMcGe GdZfG JCdja eMeO Hf YeQ Hf eMeO GdSHJi GdeYQha HGdOQGL ced hGdMeO ddg MeOkG cKjQkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B269s
Keywords: (3GdCOHs